Preferred product features among international buyers in Johor Strait Development Corridor - Chew, Lik Chee, 1992-, author; Choong, Weng Wai; Fakulti Geoinformasi dan Harta Tanah (2016)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah)) - Universiti Teknologi Malaysia, 2016